Land Suitability Evaluation for Sugar Palm (Arenga pinnata Merr.) in Nagari Labuah Gunuang, West Sumatra, Indonesia - Syahputri, Rispiza; Ikhsan, Zahlul; Rezki, Dewi (Jurusan Budidaya Perkebunan, 2025)
An evaluation of the suitability of land for sugar palm cultivation was conducted to assess the land's ability to support maximum growth and production. Palm cultivation in Nagari Labuah Gunuang, Limapuluh Kota Regency, has not been optimal because the plants still grow wild without regard to land suitability. This study aims to determine the actual and potential land suitability classes and map land suitability for palm cultivation development. This study employed a field survey using the purposive sampling method on four land units, with sample point criteria selected based on overlay results and representing each land map unit. Additionally, soil sampling was conducted at a depth of 0–60 cm, followed by laboratory analysis. Land suitability was evaluated using a matching method that matched land characteristics with the requirements for palm tree growth. Spatial analysis was then performed using ArcGIS software to produce a land suitability map. The results showed that land suitability classes in Nagari Labuah Gunuang varied. Land units 1 and 4 were classified as unsuitable because they had a slope of more than 40%, while land units 2 and 3 were classified as marginally suitable with a slope of 15–25%. The main limiting factor on land units 2 and 3 is the risk of erosion. After improvement measures such as terrace construction and planting of ground cover crops, the potential suitability class of land units 2 and 3 can be upgraded to moderately suitable. The development of sugar palm cultivation in Nagari Labuah Gunuang can be carried out on land units 2 and 3.